An Assessment of the Theme of Grace and Law in the Antitheses in Matthew 5:21–48: Implications on the Disciple-making Process (Impact: Journal of Transformation, 2020)
A reading of the Antitheses in Matthew’s Gospel record (Matthew 5:21–48) leaves one to wonder whether the demands put upon Jesus’ disciples are practically possible. This study seeks to respond to the following research questions: What function does the theme of grace and law play in the disciple-making process? How does the theme of grace and law influence the life of a disciple? The study responds to the above questions by analyzing the theme of grace and law in Matthew 5:21–48. It argues that the Antitheses follow the scheme of grace and law which is an overall theme of the Sermon on the Mount. This is to say that the demands put on Jesus’ disciples are not dependent upon their human effort but the divine empowerment to do the demands of the law. The study utilizes a hermeneutical method of socio-rhetorical interpretation of Matthew 5:17–48 and shows the implications of the theme of grace and law on the disciple-making process. The study consists of three sections. The first is a general introduction to the theme of grace and law in Matthew, and particularly in Matthew 5:21–48. The second section analyzes Jesus’ interpretation of the OT law and its implications on disciple-making. Finally, the third section is a summary and conclusion of the theme of grace and law in the disciple-making process. It reveals that the disciple of Jesus, by entering into a cooperative journey with God in following Jesus, manifests the distinctive Christian lifestyle.